2011
DOI: 10.1155/2011/715642
|View full text |Cite
|
Sign up to set email alerts
|

Loss of H2A.Z Is Not Sufficient to Determine Transcriptional Activity of Snf2-Related CBP Activator Protein or p400 Complexes

Abstract: The p400 and SRCAP (Snf2-related CBP activator protein) complexes remodel chromatin by catalyzing deposition of histone H2A.Z into nucleosomes. This remodeling activity has been proposed as a basis for regulation of transcription by these complexes. Transcript levels of p21 or Sp1 mRNAs after knockdown of p400 or SRCAP reveals that each regulates transcription of these promoters differently. In this study, we asked whether deposition of H2A.Z within specific nucleosomes by p400 or SRCAP dictates transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…However, loss of H2A.Z binding was not sufficient to stimulate p21 expression in MDA-MB231 cells. This observation correlates with previous studies showing that a 50% reduction H2A.Z association was not sufficient to induce changes in gene regulation [31].…”
Section: Discussionsupporting
confidence: 92%
“…However, loss of H2A.Z binding was not sufficient to stimulate p21 expression in MDA-MB231 cells. This observation correlates with previous studies showing that a 50% reduction H2A.Z association was not sufficient to induce changes in gene regulation [31].…”
Section: Discussionsupporting
confidence: 92%
“…However, h2a.z;pie1 double mutants exhibit early developmental arrest not seen in either of the single mutant lines, indicating that H2A.Z may be deposited in the absence of the PIE1 complex, potentially by the Arabidopsis homolog of INO80 [76], which can deposit H2A.Z in yeast [51]. The PIE1 complex might also have H2A.Z-indpendent roles, as has been hypothesized for the PIE1/SWR1 orthologs in animals [49], [50]. Indeed, a recent study showed that H2A.Z deposition by p400 and SRCAP, the human orthologs of SWR1, could not account for all the regulatory roles of these complexes [50].…”
Section: Discussionmentioning
confidence: 88%
“…There is now considerable evidence that the PIE1 complex deposits H2A.Z into chromatin in Arabidopsis, though whether it has H2A.Z-independent functions, as has been shown for other eukaryotic SWR1 homologs, remains unclear [29], [49], [50]. Other Arabidopsis chromatin remodelers are probably also able to deposit H2A.Z, as does the yeast INO80 complex [51], because H2A.Z is incorporated into nucleosomes at low levels in pie1 and swr1 mutants [29], [34], [52].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, scaffolding activities might partially explain some roles of chromatin remodelers, as suggested for SRCAP (Bowman et al, 2011). So far, our knowledge of the mechanisms of H2A.V incorporation has been anecdotal (Joyce et al, 2011;Kusch et al, 2014;Lu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%